Do Digital Literacy and Digital Entrepreneurship among University Students Contribute to Digital Economy? - Riza Primahendra; John Tampil Purba; Gracia Shinta S Ugut; Sidik Budiono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Covid-19 pandemic accelerated the digital transformation that affected people, including university student. The research intention is to know the contribution of digital literacy and digital entrepreneurship to digital economy among university student. The study used PLS-SEM and the data was collected through online questionnaire. The questionnaire was distributed among university students in Jakarta in which 103 respond and filled it. The result of the research that digital literacy influenced both digital entrepreneurship and digital economy, digital entrepreneurship influenced digital economy.